Analysis of Scara Robot program design using PLC for material handling automation system - Abdul Hakim; Risfendra (Journal of Industrial Automation and Electrical Engineering, 2025)
Industrial automation is increasingly developing in improving efficiency and productivity, one of which is the use of SCARA (Selective Compliant Articulated Robot Arm) robots. This research discusses the design and testing of SCARA robot programs for material handling automation systems based on Programmable Logic Controller (PLC). Testing is done using software and hardware, including function block diagrams, and implementation of the SCARA robot program. The test results show that the designed automation system can function optimally, with integration between the robot, conveyor, and sensors running efficiently. In addition, the robot program is able to execute commands with high accuracy, including automatic material removal. This success confirms that the system design can be applied to improve efficiency in industrial production processes.